Impact of postharvest use of essential oils on quality and shelf life of Indian pineapple - Mandal, Debashis; Vanlalawmpuia , Chhangte (Journal of Postharvest Technology, 2020)
Present study was performed to assess the effect of different essential oils viz. cinnamon, citronella, peppermint, eucalyptus, lavender, thyme,  rosemary and basil, on physico-chemical qualities and shelf life of stored pineapple cv. Giant Kew at ambient (temperature: 25±30C; relative humidity:  75±5%) condition. It was found that treatment with eucalyptus oil (0.5% v/v) significantly controlled the physiological weight loss, fruit shrinkage, textural  degradation and maintained good flesh colour (L:86.48, a:-6.64, b:39.48), translucency (score: 2.25) and crown condition (score: 1.50). Besides, after 9  days of storage; TSS (13.520Brix), titratable acidity (0.95%), total sugar (10.18%), total phenol (64.49 µg g-1), ascorbic acid (22.24 mg 100g-1) and  antioxidant activity (71.48±1.02 % inhibition DPPH) was found highest under this treatment compared with others. No fruits got decayed under this  treatment up to nine days and caused maximum shelf life (16.75 days). However, the shelf life was also high (16.25 days) for basil oil treated pineapple  fruits.
Keywords: antioxidant; decay; essential oil; eucalyptus; pineapple; shelf life